Gut microbiota metabolites in the immunoregulation of enteritis: research progress - Yu, Shaochen; Zhang, Mengjie; Dou, Ziyue; Tian, Beibei; Lu, Jian (Frontiers in Immunology, 2025)
The interaction between gut microbiota metabolites and the host immune system plays a crucial role in maintaining intestinal homeostasis and in the development of inflammatory bowel disease and other enteric conditions. This article presents a systematic review of the sources and functions of short-chain fatty acids, tryptophan metabolites, bile acids, and other microbial metabolites, focusing on how these metabolites regulate the function of immune cells, such as T cells, B cells, neutrophils, macrophages, and dendritic cells, as well as key inflammatory signaling pathways, including the NF-κB, NLRP3 inflammasome, and JAK–STAT pathways, thereby influencing intestinal barrier integrity. Also explored are potential therapeutic strategies based on microbial metabolites, including the application status and prospects of probiotic and prebiotic interventions, the direct administration of metabolites, and fecal microbiota transplantation. Although current research faces challenges such as unclear mechanisms, significant differences among individuals, and barriers to clinical translation, the development of multiomics technologies and precision medicine holds promise for providing more effective and personalized treatment strategies targeting gut microbiota metabolites for patients with enteritis.